2007
DOI: 10.1182/blood-2007-02-073213
|View full text |Cite
|
Sign up to set email alerts
|

Apaf-1 and caspase-9 deficiency prevents apoptosis in a Bax-controlled pathway and promotes clonogenic survival during paclitaxel treatment

Abstract: Taxane derivatives such as paclitaxel elicit their antitumor effects at least in part by induction of apoptosis, but the underlying mechanisms are incompletely understood. Here, we used different cellular models with deficiencies in key regulators of apoptosis to elucidate the mechanism of paclitaxel-induced cell death. Apoptosis by paclitaxel was reported to depend on the activation of the initiator caspase-10; however, we clearly demonstrate that paclitaxel kills murine embryonic fibroblasts (MEFs) devoid of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 55 publications
6
47
0
Order By: Relevance
“…Both cell lines were engineered to express control or TACC3-specific shRNAs upon doxycycline (DOX) treatment (Supplementary Material & Methods). Consistent with earlier studies (Janssen et al, 2007), prolonged treatment with increasing doses of PTX (10 and 100 nM) elicited a strong cell-death response in both MCF-7 lines that was comparable to that induced by the topoisomerase inhibitor etoposide (Figures 1a and b). As demonstrated previously (Essmann et al, 2004), exposure of the cells to gIR, on the other hand, led to a reduced apoptotic response when DNA fragmentation was determined ( Figure 1a).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Both cell lines were engineered to express control or TACC3-specific shRNAs upon doxycycline (DOX) treatment (Supplementary Material & Methods). Consistent with earlier studies (Janssen et al, 2007), prolonged treatment with increasing doses of PTX (10 and 100 nM) elicited a strong cell-death response in both MCF-7 lines that was comparable to that induced by the topoisomerase inhibitor etoposide (Figures 1a and b). As demonstrated previously (Essmann et al, 2004), exposure of the cells to gIR, on the other hand, led to a reduced apoptotic response when DNA fragmentation was determined ( Figure 1a).…”
Section: Resultssupporting
confidence: 90%
“…Thus, these data imply that the reduction of Bim expression might be the reason for the apoptosis-resistant phenotype of TACC3-depleted cells. In agreement with this hypothesis are recent reports demonstrating that Bim is an important mediator of apoptosis induced by microtubule-interfering agents such as PTX (Janssen et al, 2007;Li et al, 2007), although contrary reports also exist (Czernick et al, 2009). …”
Section: Resultssupporting
confidence: 71%
“…Lysosomal membrane permeabilization and activation of caspase-3 and calpains occur only in detached cells Next to caspases (Park et al, 2004;Ehrlichova et al, 2005;Li et al, 2005;Lu et al, 2005;Day et al, 2006;Janssen et al, 2007;Pineiro et al, 2007), involvement of calpains (Pineiro et al, 2007) and cathepsin-B (Broker et al, 2004) was described in taxol-induced apoptosis. We compared taxol-treated detached and adherent A549 cells for activation of caspase-3 and calpains on immunoblots (Figure 3a).…”
Section: Treatment With Taxol Results In Detachment and Apoptosis Of mentioning
confidence: 99%
“…The signaling pathways leading to cell death have been extensively studied (Blagosklonny and Fojo, 1999;Zhao et al, 2005) and recently several papers on the proteases involved were published. It is now clear that taxol triggers apoptosis by both caspasedependent (Park et al, 2004;Ehrlichova et al, 2005;Li et al, 2005;Lu et al, 2005;Day et al, 2006;Janssen et al, 2007;Pineiro et al, 2007) and caspase-independent pathways (Broker et al, , 2004Huisman et al, 2002;Ofir et al, 2002). One of the main supporting observations for the latter is the failure of the pancaspase inhibitor zVADfmk (N-benzyloxycarbonylVal-Ala-Asp(O-Me) fluoromethyl ketone) to protect against taxol-induced apoptosis Huisman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the apoptosome is critical for tumor suppression in a cell-specific manner and that failure of apoptosome formation may be important for tumor cell survival only in cell types unable to switch their death program from apoptosis to caspase-independent cell death. 2,66 Mitochondrial outer membrane potential (MOMP)-dependent, caspase-independent cell death may be induced by damaged mitochondrial function or by the release of mitochondrial proteins, such as AIF, Omi/HtrA2 and endonuclease G. Cell survival in spite of MOMP, in contrast, requires recovery of mitochondrial function. Live cell imaging revealed that during apoptosis some mitochondria escape MOMP.…”
Section: Caspases and Cancer M Olsson And B Zhivotovskymentioning
confidence: 99%